Grief Counseling and Crisis Intervention in Hospital Trauma Units: Counseling Families Affected by Traumatic Brain Injury. (October 2013) - Jacobson, Lamerial; Butler, S. Kent
The demand for family counselors implementing crisis intervention and grief counseling in hospital trauma units continues to increase. Thus, this article provides a review of the nature of family counselors working with individuals and families affected by traumatic brain injury (TBI) and medical trauma in hospitals. Specifically, the article presents (a) unique aspects of crisis intervention and grief services provided in hospital trauma units, (b) effective rapport building strategies for family counselors working with families in crisis from TBI, (c) multidisciplinary collaboration in hospitals, (d) diagnostic approaches and common mental health disorders following TBI, (e) ethical issues working in hospitals, (f) family-focused grief therapy and stages of grief interventions, and (g) implications with a case example of a family counselor working with a family affected by TBI.